Roles and Leadership Styles in Improving Employee Performance at the Cooperatives and Smes Service Office of South Sulawesi Province - Asraid Basman; Sangkala Sangkala; Suryadi Lambali (Enrichment : Journal of Management, 2022)
The purpose of this study was to explore the role and style of leadership in improving performance. Therefore, the leader has full duties and responsibilities in every organization he leads to improve the quality and competence of his followers. With an increase, it means that the challenges will be more severe along with the times. In this case, there are tasks, roles and leadership styles that can make the organization better and more advanced, but in reality it is still running as if the changes are stagnant or insignificant from year to year. This study uses a qualitative method with 15 key informants in the research area. The results of this study identify that exemplary who can set an example, understand the ability of followers and assign tasks to the right people can improve organizational performance.